Improving the Understanding of Pancasila and Citizenship as an Effort to Prevent the Threat of Drugs for Young Generation in Kelurahan Pangkalan Mansyur, Medan Johor - Andriati, Syarifah Lisa; Abduh, Afrita; Lubis, Rafiqoh (Talenta Publisher, 2023)
The Devotion Team set the title of the service to be